2021
DOI: 10.1038/s41467-021-23837-y
|View full text |Cite
|
Sign up to set email alerts
|

Nanomolar phosphate supply and its recycling drive net community production in the subtropical North Pacific

Abstract: Seasonal drawdown of dissolved inorganic carbon (DIC) in the subtropical upper ocean makes a significant contribution to net community production (NCP) globally. Although NCP requires macronutrient supply, surface macronutrients are chronically depleted, and their supply has been unable to balance the NCP demand. Here, we report nanomolar increases in surface nitrate plus nitrite (N+N, ~20 nM) and phosphate (PO4, ~15 nM) from summer to winter in the western subtropical North Pacific. Molar ratios of upward flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 65 publications
(101 reference statements)
2
13
0
Order By: Relevance
“…This trend is consistent with the overall pattern in climatological values from the WOA dataset (Fig. 1a) alongside other previous observations (Hashihama et al 2009(Hashihama et al , 2021Kitajima et al 2009;Shiozaki et al 2010;Martiny et al 2019). Surface N 2 fixation rates measured at the four stations demonstrated an opposite trend to that of surface DIP concentrations, with rates decreasing abruptly between the two northerly stations (1.46 and 1.15 nmol L À1 d À1 at Stas.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…This trend is consistent with the overall pattern in climatological values from the WOA dataset (Fig. 1a) alongside other previous observations (Hashihama et al 2009(Hashihama et al , 2021Kitajima et al 2009;Shiozaki et al 2010;Martiny et al 2019). Surface N 2 fixation rates measured at the four stations demonstrated an opposite trend to that of surface DIP concentrations, with rates decreasing abruptly between the two northerly stations (1.46 and 1.15 nmol L À1 d À1 at Stas.…”
Section: Resultssupporting
confidence: 91%
“…Most evidence for DIP depletion has been provided from the (sub)tropical North Atlantic, where numerous studies have demonstrated that DIP concentrations can be depleted to < 10 nmol L À1 , levels leading to microbial phosphorus stress (Wu et al 2000;Mather et al 2008;Moore et al 2008Moore et al , 2009Van Mooy et al 2009;Mahaffey et al 2014;Browning et al 2017). However, evidence has also accumulated for low DIP concentrations over a broad extent of the (sub)tropical North Pacific (Hashihama et al 2009(Hashihama et al , 2021Kitajima et al 2009;Shiozaki et al 2010;Martiny et al 2019;Browning et al 2022). This has important implications for projecting future changes of the broad oligotrophic North Pacific ecosystems, given the fact that DIP concentrations have been suggested to be declining in recent decades in this region (Kim et al 2014).…”
mentioning
confidence: 99%
“…Despite the above-described uncertainties of our calculations, our estimates are in the lower range, but in the same order of magnitude, of the only reported diapycnal P fluxes to the upper euphotic zone based on simultaneous turbulence microstructure and high-resolution chemical measurements in the oligotrophic South China Sea (Du et al, 2017) and in the subtropical North Pacific (Hashihama et al, 2021). Thus, despite hydrological differences among these oceanic regions, we assume our estimates to be valid for the purpose of the following section of this work, i.e., to assess the relative contribution of external and internal sources of phosphate to the mixed layer.…”
Section: Vertical Variability Of Phosphate Inside the Phosphate-depleted Layersupporting
confidence: 42%
“…The limitations of iron and phosphate were confirmed during both seasons. The surface phosphate level in the western NPSG was <15 nmol l −1 , regardless of the season (Hashihama et al., 2009, 2019, 2021; Kodama et al., 2011). Similarly, low levels were observed in the North Atlantic subtropical gyre (Mather et al., 2008), where diazotrophs are under phosphate limitation and colimitation of iron and phosphate (Langlois et al., 2012; Mills et al., 2004; Sañudo‐Wilhelmy et al., 2001; Turk‐Kubo et al., 2012).…”
Section: Discussionmentioning
confidence: 99%